Assess The Effect Of Incentive Spirometer On The Level Of Stress Among Patients Admitted In Cancer Hospital - Anantkumar.H, Anantkumar.H; Mondal, Priya; Heena.B, Heena.B (Journal of Neonatal Surgery, 2025)
Background of the study: It is not a shocking fact that medical centres, hospitals, and even healthcare institutions may be somewhat demanding. Having cancer changes one "s world in many different ways. Incentive Spirometer is a technique designed to help people in hospital and community environments manage stress. The Incentive Spirometer approach has been authorized by several research, hence we choose this one to investigate its effectiveness on cancer patients stress levels as previous studies support it. Goal Of the study: The main goal of the study is to find how Incentive Spirometer affects cancer patients' stress level.. Material and method: This study used the convenience sampling technique; the target population is comprised of all cancer patients over the age of 18. The study included 35 cancer patients. The Incentive Spirometer technique is a 15-day, 20-minute procedure that targets certain muscles. Then we assessed each client's level of stress. Result: Pre-test stress was high (74%), followed by extremely high (17%) and moderate (8.6%), while post-test stress was low (74%), followed by extremely high (17%) and moderate (8.6%). Paired T tests were used to assess stress. (df = 34, p=0.001). Occupation was 0.05 related to pre-test stress level. Conclusion: The Incentive Spirometer has a statistically significant effect on the difference in scores between pre- and post-test. Following the Incentive Spirometer approach, data were collected using the QSC-R10 tool.